2019
DOI: 10.1002/smj.3017
|View full text |Cite
|
Sign up to set email alerts
|

Middle management involvement in resource allocation: The evolution of automated teller machines and bank branches in India

Abstract: Research Summary: Managers at multiple levels of a firm influence resource allocation but most research focuses on senior rather than middle managers. We study involvement of middle managers in decision making, focusing on how rewards and controls shape resource allocation. We argue that higher income growth uncertainty (rewards) and lower monitoring (controls) increase resource allocation most strongly when middle managers are more involved in decisions. We test the arguments for ATM and bank branch allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…In addition to the research on the purposes of resource allocation, the research on the processes of resource allocation have culminated several prominent models describing how resources are committed to emerging markets (Christensen and Bower 1996 ), new businesses (Noda and Bower 1996 ), new customers (Danneels 2007 ), new product features (Ethiraj et al 2012 ), new locations (Natarajan et al 2019 ), and breakthrough inventions (Vinokurova and Kapoor, 2020 ). Each model focuses on specific features of the environment, specific contexts of the firm, or specific resources of the firm, as summarized in Table 3 .…”
Section: Resource Allocation As a Mechanism For Stability And Functio...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the research on the purposes of resource allocation, the research on the processes of resource allocation have culminated several prominent models describing how resources are committed to emerging markets (Christensen and Bower 1996 ), new businesses (Noda and Bower 1996 ), new customers (Danneels 2007 ), new product features (Ethiraj et al 2012 ), new locations (Natarajan et al 2019 ), and breakthrough inventions (Vinokurova and Kapoor, 2020 ). Each model focuses on specific features of the environment, specific contexts of the firm, or specific resources of the firm, as summarized in Table 3 .…”
Section: Resource Allocation As a Mechanism For Stability And Functio...mentioning
confidence: 99%
“…(2) Shaping the evaluation criteria to help attract resources required the presence of evaluative uncertainty with respect to the appropriate criteria for evaluating breakthrough inventions Vinokurova and Kapoor ( 2020 ) used historical case studies of three breakthrough inventions at Xerox-office workstations, personal computers, and laser printers, illustrating how inventors in a large firm navigated multiple evaluation criteria across different organizational units to attract resources so as to commercialize the inventors’ breakthrough inventions The process of evaluating customer requests for new product features highlights how firms respond to customer requests for incremental product innovations, and how these responses change when the requested innovation is complex Ethira et al ( 2012 ) used large sample empirical analyses combined with detailed qualitative data drawn from interviews, revealing the importance of organization structures, competitive pressures, and incentives for resource allocation processes The involvement of middle managers in the decision making about resource allocation, focusing on how rewards and controls have different associations with resource allocation depending on the level of managers involved in decision making. Higher rewards arising from uncertainty about employee income growth and lower controls based on monitoring increase resource allocation most strongly when middle managers are more involved in decisions Natarajan et al ( 2019 ) studied the allocation of ATM and bank branch (which locations and how many) in Indian commercial banks from 2011 to 2014, a high-growth environment undergoing rapid technological transformation and evolution of social goals An iterated process of resource allocation—technical personnel and testing facility being redeployed and recombined continuously between R&D and SCM—underlies the experimentations for solutions that may potentially solve the problems arising from external shocks. The solutions are generated and tested jointly between the firm and its supply chain partners as the technical personnel, from both functions, experiments iteratively with new materials, new tools, and new technologies The current study derives inductively an iterated process of resource allocation between two interdependent functions: R&D and SCM …”
Section: Resource Allocation As a Mechanism For Stability And Functio...mentioning
confidence: 99%
“…However, Natarajan et al (2019) found that resource allocation is susceptible to agency problems due to IA between decision-makers and the managers, who provide decision-makers with information about resource requirements. Busenbark et al (2017) stated that IA moderates the relationship between the firm strategic initiative and FP because these boundary conditions of IA incline to management decision for resource allocation.…”
Section: Resource Allocation Reviewmentioning
confidence: 99%
“…Reallocation isn't required at all times; but there also is surprisingly little research on specific conditions under which resource allocation flexibility influences performance. Moreover, studies of resource allocation traditionally focus on companies in the private sector (e.g., Asgari, Singh, & Mitchell, 2016; Busenbark et al, 2022; Natarajan, Mahmood, & Mitchell, 2019; Vidal & Mitchell, 2015). As a consequence, little is known about performance implications for not‐for‐profit or public colleges and universities subject to nonmarket environments 1 such as state and federal regulation 2 .…”
Section: Introductionmentioning
confidence: 99%